2018
DOI: 10.1111/ajo.12842
|View full text |Cite
|
Sign up to set email alerts
|

A clinical audit of combined first trimester screening and non‐invasive prenatal testing offered to pregnant women in a regional Australian hospital

Abstract: The records of women attending a large Australian regional hospital for antenatal care were retrospectively analysed to determine what proportion had undergone or been offered first trimester screening for fetal abnormalities; only 609 (54%) of 1114 women had undergone or been offered screening. Younger women, multiparous women and women living in rural Australia were less likely to be offered screening. Barriers to screening and solutions for overcoming these need to be identified to improve access and equali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…NIPT is taken up more widely by the 30% of pregnant people who receive private obstetric care; approximately 50-75% of people in this group are thought to choose NIPT (usually as a first-tier test), compared with 25% in the public system (53). Those who access NIPT tend to be older and to live in metropolitan areas and areas of greater socioeconomic advantage (2,70).…”
Section: Australiamentioning
confidence: 99%
“…NIPT is taken up more widely by the 30% of pregnant people who receive private obstetric care; approximately 50-75% of people in this group are thought to choose NIPT (usually as a first-tier test), compared with 25% in the public system (53). Those who access NIPT tend to be older and to live in metropolitan areas and areas of greater socioeconomic advantage (2,70).…”
Section: Australiamentioning
confidence: 99%
“…Also, the test is not reimbursable through private health insurance. Previous studies in this country show that women who opt for NIPT tend to live in metropolitan areas and areas of greater socioeconomic advantage, 44,45 justifying concerns of inequity by sociodemographic background. In Canada, variability exists in NIPT funding models within the country 2 .…”
Section: Discussionmentioning
confidence: 98%
“…In 2018, we found that 54% of women in Far North Queensland (FNQ) giving birth in Cairns Hospital had not been offered prenatal screening, findings consistent with several other studies of women in rural areas. [2][3][4] We therefore undertook a study of FNQ general practitioners (GPs) and private obstetricians (POs), to investigate this apparent under-screening.…”
Section: Barriers and Potential Solutions To Improve Access And Equity In Prenatal Screening For Rural Womenmentioning
confidence: 99%